Clinicopathological Characteristics of Hirschsprung’s Disease: A Single-Center Study in Bangladesh - Chakraborty, Debashis; Rahman, SM Mahfuzur; Sufian, Abu; Rahaman, Md Arifur; Alam, Md Mazharul (Eastern Medical College Journal, 2024)
Background: Hirschsprung disease (HD) is the congenital absence of parasympathetic ganglionic cells within the distal intestine. This leads to a lack of gut motility, stool stasis, and constipation. HD is relatively common in children. This study aims to identify the clinic-pathological characteristic of HD patients in our institution in Bangladesh. Materials and Methods: This cross-sectional observational study was carried out in the department of pediatric surgery, Mymensingh Medical College Hospital, Mymensingh from January 2018 to April 2019with ethical clearance from respective IERB. Sixty cases of clinically, radiologically consistent with Hirschsprung’s Disease not in acute stage, chronic constipation with assisted defecation in older children and children who came with colostomy for subsequent management without tissue diagnosis were purposively included in the study. In each case information about the patients was obtained in a predesigned questionnaire after obtaining written consent of the parents/guardians in the consent form. All the patients underwent rectal punch biopsy. Variables were expressed as mean ± SD, frequency and percentage. Results:The age range of the study group was 3 days to 7 years with a mean age of 1.20±1.90 years. Among the 60 patients 40 (66.6%) patients were male and the rests 20 (33.4%) were female with a ratio of 2:1. Most of the patients were in neonatal period (25, 41.66%) followed by infants (18, 30%). In this study. In the study cases delayed passage of meconium was in 42 patients, constipation was in 58 patients, abdominal distensions were in 42 patients, vomiting was in 25 (41.66%) patients. Conclusion:The clinical presentation of Hirschsprung’s disease ranges from neonatal intestinal obstruction to chronic progressive constipation in older children. It is hoped that early presentation and diagnosis of the disease enhance early surgical correction and prevent fatal complications among the children. Eastern Med Coll J. July 2024; 9 (2): 91-94